Cocaine-Induced Posterior Reversible Encephalopathy Syndrome (PRES): A Case Report Highlighting Neurological and Clinical Outcomes - Griškaitė, Patricija; Kvaščevičienė, Eleonora; Laubner Sakalauskienė, Gabija (Acta medica Lituanica, 2025)
Background: Posterior reversible encephalopathy syndrome (PRES) is a rare neurological condition characterized by disrupted cerebral autoregulation, often associated with clinical features such as hypertension, encephalopathy, seizures, and visual disturbances. Although it primarily affects females aged 20–65, posterior reversible encephalopathy syndrome can present across diverse demographics. This case underscores the critical importance of identifying uncommon risk factors to facilitate early diagnosis and optimal management.Clinical case: A 37-year-old male with stage 3 chronic kidney disease secondary to hereditary nephropathy and a history of cocaine and alcohol misuse presented to the emergency department with recurrent seizures, hypertension, hyperthermia and altered consciousness. Imaging demonstrated cortical-subcortical hypodensities on CT and parieto-occipital FLAIR hyperintensities on MRI, consistent with the diagnosis of PRES. A diagnosis of PRES was confirmed based on the patient’s history, neurological evaluation, and characteristic radiological findings.Conclusions: Raising awareness of PRES and its less recognized but increasingly relevant risk factors, such as stimulant drug use – particularly cocaine – remains a critical aspect of improving diagnostic accuracy and management. Although PRES is typically reversible, delayed diagnosis and treatment may lead to permanent neurological complications, including cerebral infarction and hemorrhage.